Protamine Promotes Direct Electron Transfer Between Shewanella oneidensis Cells and Carbon Nanomaterials in Bacterial Biocomposites. Issue 9 (12th March 2019) - Pinck, Stéphane; Jorand, Frédéric P. A.; Xu, Mengjie; Etienne, Mathieu
Abstract: In this work, we studied the direct electron transfer reactions occurring in a biocomposite resulting from the self‐assembly of Shewanella oneidensis MR‐1 cells with different carbon nanomaterials (multi‐walled carbon nanotubes, graphene oxide, Ketjen black or ordered mesoporous carbon) and protamine. The system has been studied with dynamic light scattering, scanning electron microscopy, epifluorescence microscopy and electrochemistry. Although protamine is known to have an antimicrobial activity, the interaction with carbon nanomaterials largely limits this effect. Formate and lactate oxidation and fumarate reduction have been studied. In the presence of 50 mM formate or 50 mM fumarate, the anodic current was lower than the cathodic one with the biocomposite prepared with protamine, while it was found similar with the biocomposite prepared with cytochromes c1 or c3 DvH, suggesting different electron transfer pathways. The redox potential observed for fumarate reduction (half‐wave potential) was found between −0.1 V and −0.2 V vs. SHE with an onset potential close to 0 V vs. SHE with MWCNT, i. e. very close to 0.030 V vs. SHE, the formal redox potential for fumarate/succinate interconversion. A maximum current density in the range of 1 A m −2 was reached for fumarate reduction. These data highlight a new way to promote direct electron transfer reactions in electroactive artificial biofilms. Abstract : Protamine induces the self‐assembly of Shewanella oneidensis cells with carbon nanomaterials such as multiwalled carbon nanotubes or Ketjen black. The biocomposites that are produced can be deposited on electrodes to serve as electroactive artificial biofilms. Direct electron‐transfer reactions are promoted by protamine in these biofilms and maximum current densities of the order of 1 A m −2 are reached for fumarate reduction.